2006
DOI: 10.1089/acm.2006.12.59
|View full text |Cite
|
Sign up to set email alerts
|

Abnormally High Plasma Levels of Vitamin B6 in Children with Autism Not Taking Supplements Compared to Controls Not Taking Supplements

Abstract: Total vitamin B6 is abnormally high in autism, consistent with previous reports of an impaired pyridoxal kinase for the conversion of pyridoxine and pyridoxal to PLP. This may explain the many published studies of benefits of high-dose vitamin B6 supplementation in some children and adults with autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 15 publications
1
57
0
Order By: Relevance
“…Therapy with vitamin B 6 reduces homocysteine levels and appears to improve the symptoms experienced by chronic schizophrenic patients (18,42). Another study found that children with the autism spectrum show consistently higher concentrations of primary B 6 vitamers and significantly lower levels of PLP as compared with normal subjects (15). This study concluded that the autistic patients probably have defective PL kinase that was unable to metabolize the primary vitamers into PLP.…”
Section: The Pnp Oxidase R229w Mutation Alters the Conformation Of Kementioning
confidence: 84%
“…Therapy with vitamin B 6 reduces homocysteine levels and appears to improve the symptoms experienced by chronic schizophrenic patients (18,42). Another study found that children with the autism spectrum show consistently higher concentrations of primary B 6 vitamers and significantly lower levels of PLP as compared with normal subjects (15). This study concluded that the autistic patients probably have defective PL kinase that was unable to metabolize the primary vitamers into PLP.…”
Section: The Pnp Oxidase R229w Mutation Alters the Conformation Of Kementioning
confidence: 84%
“…Increased glutamate levels in autism could be explained by presence of low levels of Pyridoxal Phosphate (PLP) in children with autism due to very low activity of pyridoxal kinase leading to blockage of glutamate utilization [32]. Also, alterations in the glutamate transporter or in glutaminase or glutamine synthetase activity would potentially affect glutamate levels [33].…”
Section: Discussionmentioning
confidence: 99%
“…Like NEE, several other neurological disorders, including seizures, autism, attention deficit hyperactive disorder, Alzheimer's, Down Syndrome, schizophrenia, Parkinson's, learning disability, anxiety disorders have also been associated with PLP deficiency [45,[84][85][86][87][88][89]. This has inspired considerable interest in treating the symptoms of some of these disorders with vitamin B 6 .…”
Section: Discussionmentioning
confidence: 99%